Admission Selection Decision Support System New Students Use the Vikor Method - Nawas, Angelita; Kiswanto, Rahmat H. (International Journal of Computer and Information System (IJCIS), 2024)
This study aims to develop a decision support system (SPK) for the selection of new students at YPPK Christ Raja Junior High School in Jayapura using the Vikor (Multi-criteria Decision Analysis) method. The main problem faced by the school is the selection process of new students who still use a manual system, causing errors in decision making. The vikor method was chosen because it is efficient in handling multi-criteria problems. This study involved 15 students as an alternative sample in the selection process. The vikor method is used for normalization, calculation of utility measure (s) and regret measure (r) values, as well as determination of index values. The ranking results are based on the s, r, and q sequences, with the best alternative solution determined based on the minimum q value. The results showed that recommendations for new student admission decisions can be obtained by utilizing the ranking results from the vikor method. The system development process is carried out using the waterfall method with stages of software requirements analysis, design, program code creation, and testing. System design is carried out using structured design, while testing uses the blackbox method. The results of this study are expected to improve the efficiency and accuracy of the selection process for new students at YPPK Christ Raja Junior High School in Jayapura through the implementation of a decision support system with the vikor method.